War and self-defense: a critique and a proposal (Diametros, 2010)
Discussions of the ethics of war commonly – and reasonably – assume that defensive wars are morally justified if any wars are. They also assume that explanations of why defensive warfare is morally justified must be based on principles that also explain the moral justifiability of individual self-defense. David Rodin has recently argued that the second of these assumptions is mistaken, and he has developed an alternative account of the morality of defensive warfare. The purpose of this paper is to show that Rodin’s argument fails, and to explain how defensive warfare can indeed be justified in terms of principles that also apply to individual self-defense.